Bacterial diversity shift determined by different diets in the gut of the spotted wing fly Drosophila suzukii is primarily reflected on acetic acid bacteria. Issue 2 (13th March 2017) - Vacchini, Violetta; Gonella, Elena; Crotti, Elena; Prosdocimi, Erica M.; Mazzetto, Fabio; Chouaia, Bessem; Callegari, Matteo; Mapelli, Francesca; Mandrioli, Mauro; Alma, Alberto; Daffonchio, Daniele
Summary: The pivotal role of diet in shaping gut microbiota has been evaluated in different animal models, including insects. Drosophila flies harbour an inconstant microbiota among which acetic acid bacteria (AAB) are important components. Here, we investigated the bacterial and AAB components of the invasive pest Drosophila suzukii microbiota, by studying the same insect population separately grown on fruit‐based or non‐fruit artificial diet. AAB were highly prevalent in the gut under both diets (90 and 92% infection rates with fruits and artificial diet respectively). Fluorescent in situ hybridization and recolonization experiments with green fluorescent protein (Gfp)‐labelled strains showed AAB capability to massively colonize insect gut. High‐throughput sequencing on 16S rRNA gene indicated that the bacterial microbiota of guts fed with the two diets clustered separately. By excluding AAB‐related OTUs from the analysis, insect bacterial communities did not cluster separately according to the diet, suggesting that diet‐based diversification of the community is primarily reflected on the AAB component of the community. Diet influenced also AAB alpha‐diversity, with separate OTU distributions based on diets. High prevalence, localization and massive recolonization, together with AAB clustering behaviour in relation to diet, suggest an AAB role in the D. suzukii gut response to diet modification.